Tariel Putkaradze and Kutaisi - Khachapuridze, Luiza (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2020)
The Scientific-Research Institute of Dialectology was established in Kutaisi in December 1992. It was later renamed the „Institute of Kartvelian Dialectology“, later it was named. „Kartvelological Dialectology“. Today it is the „Scientific-Research Center of Kartvelology“. The only annual international symposium in Georgia called „Kutaisi Conversations“ - Linguistic-Ethnological-Cultural-Scientific Scientific Forum of Kartvelologists became a remarkable event of the Institute of Dialectology in the 90s; Tariel Putkaradze was able to hang the fire of his soul for the protection of the souls of others and that is why Kutaisi and Akaki Tsereteli State University became the center of scientific research and international symposia. Representatives of scientific centers of our country and abroad, Georgian scientists working abroad, as well as foreign Kartvelologists took part in the symposium. 26 symposiums have been held so far. „Kutaisi Conversations“ laid the foundation for the scientific journal „Kartvelian Heritage“. The collection traditionally publishes symposium materials, peer-reviewed Kartvelological (linguistic, literary, folklore, ethnological, cultural ...) researches, Kartvelian dialects written by the groups of researchers of the Kartvelian Dialectology Research Center. 25 volumes have been published to date. By the initiative of T. Putkaradze, the newspapers „Kartuli“ and „Kuji“ were published in Kutaisi. In 1996, he established the Kutaisi Division of the State Chamber of the Georgian Language, and in 1998, he also founded the newspaper „Kartuli“, which operated under the Division until 2003. A total of 39 issues were published. When the opposition newspapers „Georgian Bell Tower“, „Iberia Spectrum“ were closed in Georgia, in 2000 the newspaper „Kuji“ of the Helsinki Union was born in Kutaisi - Putkaradze was the editorr-in-chief; The newspaper has existed for two years, 38 issues have been published. T. Putkaradze together with Merab Gvazava founded the Scientific Conference of the Public Library (today it is the 12th conference in a row); His scientific journal „Yearbook“ has been published in 11 volumes so far. It can be said that all this was a sunny night in Kutaisi at that time and the creator of these cases was 32 years old in 1992. This year he turned 60 years old. We thank you, as a grateful student, for your service and love for my city, Kutaisi has been his city for a long time and he is an honorary citizen.